LA PERFORMATIVITE DES NOUVEAUX MODELES MANAGERIAUX DANS LES ENVIRONNEMENTS NUMERIQUES : DISCOURS TECHNOLOGIQUES EN SANTE - Belhouchet, Zoubir (Journal of Human Sciences, 2022)
Managerial discourse constitutes a true genre and represents a particular category of performative statements. This study attempts to clarify the problematics of performativity by bringing it closer to the institutional theory of John Rogers Searle, the writings on pragmatics and the work of Benoit Cordelier on engagement and discourse. Performativity is defined as a particular type of function assignment. This approach allows us to distinguish two types of limits to the phenomena underlying the concept of performativity: raw facts and institutional facts.    Our research takes place within the framework of a health organization which develops a project of computerization of all the tasks by the use of the national health information system (SNIS).    We will see how the managerial discourse can be mobilized to convince the partners of this organization to act in the direction sought by it, especially when they are involved in a mission as delicate as that of a corporate restructuring. The challenge here is to observe how this discourse proceeds to impose itself and defeat internal resistance to the organization.